Inhibition of radical reactions for an improved potassium tert‐butoxide‐promoted 11C‐methylation strategy for the synthesis of α‐11C‐methyl amino acids12. (18th February 2015) - Suzuki, Chie; Kato, Koichi; Tsuji, Atsushi B.; Zhang, Ming‐Rong; Arano, Yasushi; Saga, Tsuneo
Abstract : α ‐ 11 C‐Methyl amino acids are useful tools for biological imaging studies. However, a robust procedure for the labeling of amino acids has not yet been established. In this study, the 11 C‐methylation of Schiff‐base‐activated α ‐amino acid derivatives has been optimized for the radiosynthesis of various α ‐ 11 C‐methyl amino acids. The benzophenone imine analog of methyl 2‐amino butyrate was 11 C‐methylated with [ 11 C]methyl iodide following its initial deprotonation with potassium tert ‐butoxide (KO t Bu). The use of an alternative base such as tetrabutylammonium fluoride, triethylamine, and 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene did not result in the 11 C‐methylated product. Furthermore, the KO t Bu‐promoted 11 C‐methylation of the Schiff‐base‐activated amino acid analog was enhanced by the addition of 1, 2, 4, 5‐tetramethoxybenzene or 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl (TEMPO) and inhibited by the addition of 1, 10‐phenanthroline. These results suggest that inhibition of radical generation induced by KO t Bu improves the α ‐ 11 C‐methylation of the Schiff‐base‐activated amino acids. The addition of a mixture of KO t Bu and TEMPO to a solution of Schiff‐base‐activated amino acid ester and [ 11 C]methyl iodide provided optimal results, and the tert ‐butyl ester and benzophenone imine groups could be readily hydrolyzed to give the desired α ‐ 11 C‐methyl amino acids with a high radiochemical conversion. This strategy could be readily applied to the synthesis of other α ‐ 11 C‐methyl amino acids. Abstract : We radiosynthesized 2‐amino‐2‐[ 11 C]methyl butyric acid via 11 C‐methylation of Schiff‐base‐activated precursors and subsequent deprotections. Not only 1, 2, 4, 5‐tetramethoxybenzene or 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl (TEMPO) improved the potassium tert ‐butoxide (KO t Bu)‐promoted 11 C‐methylation of the recursors, but also 1, 10‐phenanthroline retarded the reaction. KO t Bu‐promoted 11 C‐methylation of benzophenone imine analogs of amino acid ester in the presence of TEMPO could be readily applied to the synthesis of other α ‐ 11 C‐methyl amino acids.